The Effectiveness of Probing Prompting Models for Critical Thinking Development in Indonesian Science Education: A Systematic Literature Review - Rohman, Rohil Lila; Susantini, Endang; Raharjo, Raharjo; Makhtar, Muaz Mohd Zaini; Satriawan, Muhammad (FKIP Universitas Lampung, 2025)
This study aims to systematically examine the trends, focus areas, and effectiveness of the Probing Prompting learning model in improving students’ critical thinking skills within Indonesian science education. Using the Systematic Literature Review (SLR) method based on the PRISMA protocol, 20 peer-reviewed articles published between 2020 and 2024 were selected from Scopus, SINTA, and Google Scholar databases. The inclusion criteria focused on empirical studies applying the Probing Prompting model in science learning contexts with clear outcomes related to critical thinking skills development. To enhance the analytical depth, bibliometric mapping was conducted using VOSviewer to visualize keyword patterns, thematic clusters, and the centrality of research topics in the field. The results show that the Probing Prompting model is most effectively implemented at the junior high school level, aligning with students’ cognitive development at the formal operational stage. Key strategies include structured sequential questioning and the use of students’ worksheets that guide students through reasoning and reflection. Dominant indicators of critical thinking skills developed through this model are analysis, evaluation, and inference. Visualizations reveal that “critical thinking” and “probing prompting” are among the most frequently occurring and central keywords, emphasizing their strong association in recent literature. This review also identifies emerging clusters related to digital integration, local wisdom, and artificial intelligence, suggesting future directions for contextualized and technology-supported applications of the model. It concludes that the Probing Prompting model has strong potential to be further developed as a critical thinking skills-oriented strategy, particularly in science education. The study recommends future research to conduct quantitative meta-analyses, explore long-term impacts through longitudinal studies, and integrate the model with project-based and digital learning frameworks to enhance effectiveness and sustainability. Keywords: probing prompting, critical thinking skills, science learning, SLR, VOSviewer.